2010
DOI: 10.5625/lar.2010.26.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Korean Red Ginseng Extract on Atopic Dermatitis in NC/Nga Mice

Abstract: Atopic dermatitis (AD) is a chronic eczematous skin disease attended by pruritus, erythema, edema, excoriation, and dryness. This study was to evaluate the effects of Korean red ginseng (RG) on AD in NC/ Nga mice treated with 1-chloro-2,4,6-trinitrobenzene (picryl chloride; PC). Experimental groups were divided into 4 groups; normal control (NC), PC control, and PC-RG (50 and 100 mg/kg). RG was orally administered every day repeatedly during 6 weeks. The skin lesions in severity score, scratching behavior, ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…It has been reported that increase in thickness of epidermis is caused by hyperkeratosis accompanying abnormal keratosis as well as hyperplastic cells (Zhou et al, 2014). In other previous reports, herb extracts (Lee et al, 2008), magnesium rich ocean mineral water (Kim et al, 2008), ginsengs (Kim et al, 2010), chamomile oil (Lee et al, 2011), Hwangnyeonhaedok-tang (Ki et al, 2013) were also effective to decrease the epidermis thickness as shown in the present study. Mast cells are produced from hematopoietic stem cells and travel to tissues via blood stream; depending upon the cytokine levels and types, these cells can be proliferated and modified (Shukla et al, 2005;Choi et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that increase in thickness of epidermis is caused by hyperkeratosis accompanying abnormal keratosis as well as hyperplastic cells (Zhou et al, 2014). In other previous reports, herb extracts (Lee et al, 2008), magnesium rich ocean mineral water (Kim et al, 2008), ginsengs (Kim et al, 2010), chamomile oil (Lee et al, 2011), Hwangnyeonhaedok-tang (Ki et al, 2013) were also effective to decrease the epidermis thickness as shown in the present study. Mast cells are produced from hematopoietic stem cells and travel to tissues via blood stream; depending upon the cytokine levels and types, these cells can be proliferated and modified (Shukla et al, 2005;Choi et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…In particular, fraction 2 showed the best results among the three fractions and increased IL-4 expression by 2.8-fold. However, this activity could have a harmful effect on patients with atopic dermatitis since the excessive expression of IL-4 induces allergic reactions [ 18 ].…”
Section: Discussionmentioning
confidence: 99%